Examining The Obstacles Encountered By Financial Institutions In Gondia District During The Implementation Of Agricultural Schemes (Journal of Namibian Studies : History Politics Culture, 2023)
This survey of the most cutting-edge areas of innovative research and technology aims to do two things: (a) identify the primary reasons and financial hurdles that prevent innovations from being implemented in the agricultural sector; and (b) propose solutions that will help draw on international expertise and boost innovations' access to funding. Therefore, the focus of this study is on the agricultural industry in India and, more specifically, on agricultural enterprises. The study employed logical and compared techniques for execution and developments funding estimates throughout research, as well as according to these approaches identified arena provision for investments inaction, developments financing mechanisms flaws driven, as well as there were severe governmental base complaint as well as high degree of developments risk associated with implementation found out. According to the available data, the strict, reliable, and transparent framework of financial support for innovative activities has not yet been established. It's important to keep in mind that most innovation funding is haphazard, nonsystematic, and residual.